RIG-I-like receptors direct inflammatory macrophage polarization against West Nile virus infection - Amy E. L. Stone (Nature Portfolio, 2019)
RIG-I- like receptors (RLRs) play an important role in immune defense against West Nile virus (WNV). Here, using a systems biology approach, the authors show that macrophage polarization to a proinflammatory M1 phenotype via RIG-I and MDA5 signaling is critical for innate immune control in WNV-infected mouse tissues.